Cross‐Encoded Quantum Key Distribution Exploiting Time‐Bin and Polarization States with Qubit‐Based Synchronization. Issue 12 (17th October 2022) - Scalcon, Davide; Agnesi, Costantino; Avesani, Marco; Calderaro, Luca; Foletto, Giulio; Stanco, Andrea; Vallone, Giuseppe; Villoresi, Paolo
Abstract: Robust implementation of quantum key distribution requires precise state generation and measurements, as well as the choice of an optimal encoding to minimize channel disturbance. Time‐bin encoding represent a good candidate for fiber links as birefingence does not perturb this kind of states whereas stable and low‐error encoders and decoders are available for polarization encoding. Here a cross‐encoded scheme where high accuracy quantum states are prepared through a self‐compensating, calibration‐free polarization modulator and transmitted using a polarization‐to‐time‐bin converter is presented. The receiver performs time‐of‐arrival measurements in the key‐generation basis and converts qubits back to polarization encoding for measurements in the control basis. Temporal synchronization between the transmitter and receiver is performed with a qubit‐based method that does not require additional hardware to share a clock reference. The system is tested in a 12‐h run and demonstrates good and stable performance in terms of key and quantum bit error rates. The flexibility of this approach represents an important step toward the development of hybrid networks with both fiber‐optic and free‐space links. Abstract : A novel quantum key distribution system combines the qualities of polarization and time‐bin encodings to offer unprecedented levels of flexibility in the development of quantum networks. This cross‐encoded approach allows for straightfoward qubit conversion to enable optimal encoding for any quantum channel. Furthermore, a qubit‐based synchronization algorithm is used for the first time in time‐bin encoded quantum communications.